In-memory computing - Swaminathan, Aravind Raj (Nanyang Technological University, 2022)
Neural networks are a subset of machine learning that are currently rapidly being deployed for various purposes, propelling the growth of science and technology. Current hardware limitations prove to be a challenge for efficient neural network implementations due to lack of several bottlenecks. Neural hardware accelerators are currently being researched and developed to aid in the training and deployment of neural networks.